Fragilidad y calidad de vida del adulto mayor en tiempos de COVID 19 en centros de salud Iquitos, año 2022 - Pipa Barbaran, Deisy Lucia (2025)
This research aimed to determine the relationship between frailty and quality of life in older adults during the Covid-19 pandemic in health centers in Iquitos in 2022. This was a quantitative, descriptive, correlational, and cross-sectional study, which worked with a sample of 337 older adults. Data was collected through interviews and surveys using the Edmonton Frail Scale (EFS) and the SF-12V2 questionnaire for health-related quality of life. The data was analyzed using the SPSS statistical program version 24.0. When applying the non parametric Kolmogórov-Smirnov test, a normal distribution was found in the entire sample, obtaining a p <0.00. In other words, both variables have a normal distribution. The results obtained show that 62.9% were between 60 and 74 years old, of which 37.1% were married and 18.7% were cohabiting; the educational levels with the highest percentages were primary (43.0%) and secondary (32.6%). According to the type of insurance, 68.0% had SIS and 31.5% had EsSalud. In the quality of life variable, it was observed that 83.4% had good quality of life, while 16.6% were classified as poor quality; similarly, in the frailty variable, 61.7% were evaluated as not frail, 26.1% as vulnerable, with a predominance of females (17.2%), 7.7% with mild frailty, and 2.4% and 2.1% with moderate and severe frailty, respectively. Conclusion: There is a statistically significant association between frailty and quality of life in older adults in this study.